Diffusion of neutral solutes within human osteoarthritic cartilage: Effect of loading patterns - Haoye Meng (Journal of Orthopaedic Translation, 2020)
Objective: Variation of the solute diffusion within articular cartilage is an important feature of osteoarthritis (OA) progression. For in vitro study of monitoring of the diffusion process, it is essential to simulate physiological conditions as much as possible. Our objective was to investigate the effects of loading patterns on diffusion processes of neutral solutes within osteoarthritic cartilage. Methods: Osteochondral plugs were harvested from human tibial plateaus and separated into three OA stages according to modified Mankin scoring system. The samples were subjected to static or cyclic compression using a carefully designed loading device. Contrast-enhanced micro-computed tomography (CEμCT) was applied to acquire image sequences while the cartilage was being compressed. The apparent diffusion maps and diffusion coefficients were analysed, as well as histological and stereological assessments of the plugs. Results: The diffusion of neutral solutes was significantly affected by the loading patterns. For OA cartilage with early and middle stages, cyclic loading accelerated contrast agent infiltration compared with static loading. However, for late-stage OA samples, no acceleration of diffusion was observed in the first 2 ​h because of the insufficient resilience of compressed cartilage. The accumulation of neutral solutes in an upward invasive fissure also suggested that solutes could penetrate into the fissure under cyclic loading. Conclusions: To our knowledge, this is the first study to combine the cyclic compression and CEμCT scanning in the diffusion testing of human OA cartilage. This loading pattern could simulate the physiological conditions and reduce the time to reach solute equilibrium within cartilage. The diffusion data may contribute to joint drug-injection therapies for early OA. The translational potential of this article: The combination of cyclic loading and CEμCT scanning enabled diffusion analysis of osteoarthritic cartilage under different compressions. A comprehensive evaluation of OA cartilage and subchondral bone may benefit from this technique. The diffusion data provide theoretical support and reference for intra-articular injection of drugs.